Nouman Ali Khan and the Rhetoric of Revelation: Rethinking Qur’anic Interpretation in the Digital Era - Pakal, Almohaimin Tacbil (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2024)
In recent years, there has been growing interest in how Islamic knowledge is disseminated in the digital age, particularly through charismatic figures who blend traditional learning with modern communication strategies. One such figure is Nouman Ali Khan, a prominent and influential Muslim speaker known for his engaging and accessible approach to Qur’anic interpretation. Despite his wide-reaching impact, academic analysis of Khan’s contribution to contemporary Qur’anic discourse remains limited. This study seeks to address that gap by examining his exegetical strategies and primary areas of focus in his interpretive work. Using qualitative methods, it analyzes data collected from various sources, including social media platforms, public lectures, and scholarly references to Khan’s teachings. Unlike classical exegetes who often draw on theology, jurisprudence, and philosophy, Khan concentrates on the linguistic and rhetorical dimensions of the Qur’an. His interpretive emphasis lies in the eloquence of the Qur’anic text—its word choice, structure, thematic shifts, and stylistic beauty—rather than on legal or theological implications. He highlights features such as the rhythm, sequence, and subtle changes in wording to reveal the Qur’an’s moral and spiritual lessons. This unique focus has made his work especially resonant among audiences seeking a deeper yet accessible understanding of the Qur’anic message.